SEGMENTASI KONSUMEN DEPOT MAKANAN INDONESIA DI SURABAYA - Sheila Handriyani; Olivia Vinka Imanda; Monika Kristanti (Jurnal Hospitality dan Manajemen Jasa, 2016)
Penelitian ini berfokus pada upaya untuk mengenal lebih jauh profil konsumen depot makanan Indonesia di Surabaya. Total sampel dari penelitian ini sebanyak 460 orang dengan menyebarkan kuesioner di 42 depot makanan Indonesia di Surabaya. Proses analisa data dalam penelitian ini menggunakan analisa faktor dan analisa cluster dengan SPSS. Hasil dari penelitian untuk segmentasi konsumen makanan Indonesia di Surabaya, terbentuk 3 cluster, yaitu commoners, experiencer service quality seeker, dan price & value seeker. This study focused on segmenting consumer of small Indonesian food restaurants in Surabaya. The total sample was 460 people by distributing the questionnaires to 42 small sized Indonesian food restaurants, operated throughout the regions of Surabaya with the total respondents of 460 people. Data processing methods that was used in this study were factor analysis and cluster analysis with SPSS. Result showed the consumers segmentation of small sized Indonesian food restaurant in Surabaya would be classified into 3 clusters which are commoners, experiencer service quality seeker, and price & value seeker.